Analysis of risk factors of axial neck pain in posterior cervical single-door laminoplasty from the perspective of cervical sagittal plane - Zuo, Kang Kang; Qin, Wei; Miao, Yu; Zhu, Lei (Frontiers in Surgery, 2022)
Abstract Object We carried out the study to explore the possible relationship between the cervical sagittal parameters in radiological images and axial neck pain (ANP) for patients undergone posterior cervical single door laminoplasty. Method 141 patients were enrolled in the study from January 2018 to January 2021, among which 38 were enrolled into ANP group and 103 were enrolled into non-ANP group. C2-7 Cobb angle, C2-7 sagittal vertex axis (SVA), thoracic inlet angle (TIA), neck tilt (NT), and T1 slope were measured on computed tomography (CT). Spearman correlation tests were used to analyze the possible correlation between radiological parameters and ANP. Logistic regression was carried out to analyze the potential risk factor for the occurrence of ANP. Receiver operating characteristic (ROC) curve and area under the ROC curve (AUC) were used to evaluate the significant result and the optimal diagnostic value. Results As for radiographic parameters in sagittal plane, the results suggested that only T1 slope and C2-7 SVA were statistically different between ANP and non-ANP group (p=0.001 and p=0.047). Patients whose surgery involved in C2 spinous process demonstrated severe ANP symptoms than patients in non-ANP group (p=0.003). Spearman correlation test showed that no statistical differences were found between VAS and radiological morphology parameters and only C2 involvement was found to correlate with post-operative VAS with respect to surgery. Logistic multivariate regression analysis demonstrated that only C2 involvement and T1 slope were significantly different when included C2-7 SVA, T1 slope, C2 involvement together into consideration, with a p value of 0.01 and 0.001. Conclusion According to our research, C2 involvement and greater T1 slope were independent risk factors of ANP for the patients who underwent laminoplasty of cervical spine.